Infection with novel duck reovirus induces stress granule and methylation-mediated host translational shutoff in Muscovy ducklings - Tao Yun; Jionggang Hua; Liu Chen; Weicheng Ye; Zheng Ni; Yinchu Zhu; Cun Zhang (Communications Biology, 2024)
Abstract The recently identified novel duck reovirus (NDRV) is a waterfowl reovirus that can seriously harm or kill various waterfowl species. However, how NDRV interacts with host cells in Muscovy ducklings beyond the typical pathogenesis resulting from a viral infection is unknown. The current study examined the global translation efficiency of the Fabricius bursa of Muscovy ducklings infected with NDRV HN10 using mass spectrometry and ribosome footprint sequencing. Protein-protein interactions were investigated using immunogold labeling, transmission electron microscopy, and immunocytochemistry. An analysis of the relationship between m6A and translation was performed using RNA immunoprecipitation and m6A methylation immunoprecipitation. We found that both in vivo and in vitro, the translation efficiency of RNA modified with m6A could be significantly reduced by σB, a structural protein component of NDRV HN10. Furthermore, σB might simultaneously interact with the stress granule complex CAPRIN1 and G3BP1 and the m6A reader protein YTHDF1/3. Significant overlap was observed between m6A-modified and G3BP1-enriched RNA, indicating that granule stress could capture m6A-methylated RNA. We discovered a new function for NDRV HN10 in translational shutoff by recruiting m6A-modified RNA into stress granules located in the Fabricius bursa of Muscovy ducklings.